ANALISIS SISTEM PEMASARAN GABAH/BERAS (Studi Kasus Petani Padi di Sumatra Utara) - ADE SUPRIATNA (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2005)
This study was conducted in 2002 and took place in North Sumatra.Districts of Asahan and Simalungun were chosen as area samples. The objectives ofstudy were (i) to describe the channel of rice marketing, (ii) to analyze thecomponents of cost and marketing margin in each agent of marketing link, and (iii) toidentify the characteristics and problems in each agent of marketing link. The methodof Participatory Rural Appraisal (PRA) was used in this study using Snow Ball Pointwhere the farmers were placed as a start point. Primary data were collected from 50farmers, 20 traders, 4 village rice mills, and 10 rice consumers. Secondary data werecollected from Agriculture office, Institutions for Agricultural Research, and others.The results informed that, in North Sumatra there were found two channels of ricemarketing. First, farmers sell direct unhulled rice to collecting merchant thencollecting merchant sells them to large merchant (kilang). In kilang, unhulled rice isprocessed to become hulled rice then sold them to wholesalers and retailer to be soldto consumers. Second, farmers sell unhulled rice to local rice mill. In rice mill,unhulled rice is processed to become hulled rice then sold them to retailer to be soldto consumers. In the first channel, the most marketing margin happened at kilangequal to Rp.216,- with net benefit margin of Rp. 89,-/kg. In the secondary channel themost marketing margin and net benefit margin happened at the village rice mill equalto Rp.210,- and Rp.85,-/kg respectively. Some problems in agents of rice marketingwere found especially at the levels of the farmer as rice producer, the collectingmerchant, and the local rice mill.